Budget Participation Improves the Performance of Management of the Provincial Village Credit Institution (LPD) in Bali - I Nengah Suarmanayasa (International Journal of Social Science and Business, 2023)
The quality of public service could be more optimal in the government bureaucracy. This condition has implications for the performance of the apparatus staff, which usually occurs at the beginning and end of the fiscal year. This study aims to analyze the performance of the Bali LPD apparatus. This research is a causal effect (causal effect). The type of data used in this study is primary data. The population in this study was 258 Bali LPD devices. Sampling in this study was carried out using a stratified random approach. The methods used in collecting data are observation and interviews. This research instrument was through a closed questionnaire with a Likert scale. The data analysis technique used in this study is using path analysis. The analysis results are first, and budget participation has a positive and significant effect on the performance of the Bali Province LPD apparatus. Second, budget participation positively and significantly affects the authorities' performance through a budget gap. Third, budget participation positively and significantly affects the authorities' performance by clarifying the budget objectives. Third, budget participation positively and significantly affects the authorities' performance through work motivation. Fourth, budget participation positively and significantly affects the authorities' performance through organizational culture. It was concluded that budget participation positively affected apparat performance through budget stalks, clarity of budget objectives, work motivation, and organizational culture.